Experimental and theoretical study of the energy loss of Be and B ions in Zn - Cantero, Esteban Daniel (2009)
Energy-loss measurements and theoretical calculations for Be and B ions in Zn are presented. The experimental ion energies range from 40 keV/u to 1 MeV/u, which includes the energy-loss maximum and covers a lack of experimental data for these systems from intermediate to high energies. The measurements were performed using the Rutherford backscattering technique. The ab initio calculations are based on the extended Friedel sum rule–transport cross-section method for the valence electrons and the Shellwise local plasma approximation for the bound electrons. A comparison of these calculations to the present experimental data for Be and B and previous values for H, He, and Li ions on the same target is included. This confirms the applicability of the employed theoretical framework also for ions of intermediate atomic number.